Covariance Blind Detection Method Based on Eigenvector in Cognitive Radio Network - Yingxue Li; Jing Lei; Shiyuan Zhong; Chunming Huang; Chao Huang (Dianxin kexue)
As the blind detection algorithm has the shortcoming that they need information about the channel and more than two cognitive users to detect the primary user,a new blind detection algorithm based on eigenvector using the difference of correlation between the primary user signal and noise signal covariance matrix was presented,and a closed expression was derived for the probability of false alarm and threshold.The proposed method overcomes the noise uncertainty problem only with two cognitive relays and performs well without information about the channel,primary user and noise.Numerical simulations show that the new detector performs better than other detectors.